2022
DOI: 10.3389/fmicb.2022.877280
|View full text |Cite
|
Sign up to set email alerts
|

Gut Fungal Microbiome Responses to Natural Cryptosporidium Infection in Horses

Abstract: It is critical to characterize changes in the structure and composition of the host fungal community in natural Cryptosporidium infection, because it gives the possible overview of gut microbiome in host homeostasis and disease progression. A total of 168 rectal fecal samples were collected and examined using nPCR. The positive samples were double-checked using 18S rDNA high-throughput sequencing. After confirmation, ITS high-throughput sequencing was utilized to investigate the fungal community’s response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Monkeys with active infection were found to have enriched taxa associated with dysbiosis, inflammation and rapid transit time thorough the gut ( McKenney et al, 2017 ). Shifts in fungal microbiome in horses have also been observed after cryptosporidial infections ( Wang et al, 2022 ).…”
Section: Microbiome and Metabolitesmentioning
confidence: 99%
“…Monkeys with active infection were found to have enriched taxa associated with dysbiosis, inflammation and rapid transit time thorough the gut ( McKenney et al, 2017 ). Shifts in fungal microbiome in horses have also been observed after cryptosporidial infections ( Wang et al, 2022 ).…”
Section: Microbiome and Metabolitesmentioning
confidence: 99%
“…Furthermore, some studies have shown that probiotics can alleviate symptoms associated with Cryptosporidium infection, further highlighting the direct impact that the GM can have on parasitosis ( Pickerd and Tuthill, 2004 ; Sindhu et al., 2014 ; Pane and Putignani, 2022 ). GM alterations in response to Cryptosporidium infection have been described in mice ( Wang et al., 2023 ), livestock ( Mammeri et al., 2020 ; Wang et al., 2022 ; Chen et al., 2023 ), and in very young children ( Toro-Londono et al., 2019 ; Carey et al., 2021 ), but, to our knowledge, the effect of chronic cryptosporidiosis on the composition of the human microbiome has never been addressed in any immunocompromised patient. Here, we describe the first European case of chronic infection due to the Cryptosporidium parvum IIaA20G1 subgenotype in a child with primary immunodeficiency, a rare zoonotic lineage which, thus far, has only been described in a very small number of humans and livestock in Jordan, Kuwait and Iran ( Sulaiman et al., 2005 ; Nazemalhosseini-Mojarad et al., 2011 ; Hijjawi et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%